State of Palestine - Ahmad, Abdul Razaq; Chang, Da Wan; Ismail, Russayani; Lai, Yew Meng; Ayub, Zainal Amin (Springer, 2016)
Despite being in a constant state of conflict and the manifold dangers posed by the Israeli occupation, the State of Palestine has a functional education system, which includes higher education. In fact, the higher education development in Palestine has progressed at a rapid pace over the last three decades, as it continues to succeed against the odds unbowed. This chapter examines the political, security and economic situation of Palestine, to provide a context to understanding the environment that shapes the Palestinian higher education landscape and system. This is followed by a scrutiny of the higher education sector, which includes an assessment of the set of conditions and challenges that are uniquely faced by the stakeholders of higher education in Palestine, and the potentials for future development and realization of this highly passionate agenda of the Palestinian people.